Copyright violation and combating mechanisms in selected publishing houses in Ibadan, Oyo State, Nigeria (2018)
Copyright violation poses a major challenge to the publishing industry. It is a common malaise which does not only affect all the stakeholders in the book sector, but is inimical to the growth and survival of the industry. This study therefore examined the combating mechanisms adopted by selected publishing houses in curbing copyright violation in Ibadan metropolis in Oyo State, Nigeria. Descriptive survey design was adopted and the study population consisted of200 staff drawn from eight publishing houses in Ibadan. Total enumeration method was employed; questionnaire was the data collection instrument, while data was analysed using descriptive statistics for the five research questions formulated. Findings revealed that the most common forms of copyright violation were piracy and sale of publications without authors' consent while its effect include loss of income, retardation of economic growth, loss of job, and loss of reputation. The use of technology-based deterrents like internet protocol restrictions was considered best in discouraging copyright violation for electronic publications. Finding revealed that severe enforcement of copyrights law and the use ofpublic enlightenment programme are effective combating measures against copyright violation. It was recommended, among others, that government and publishers should embark on public enlightenment programme, make books affordable, and collaborate to combat copyright violation.